Database Support for Online Social Network Analysis - Pintor, Paulo; Salgueiro, Mariana D. A.; Lifschitz, Sérgio; Schwabe, Daniel; Moreira, José; Costa, Rogério (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2023: Anais do XXXVIII Simpósio Brasileiro de Bancos de Dados, 2023)
Online Social Networks (OSNs) have become part of our daily life, contributing to the vast amount of data generated online. The OSNs' data contribute to obtaining information about our society in various areas, such as misinformation, politics, marketing, and engagement metrics. OSN is a comparatively new concept, without a generic model, with problem-specific models used for the studies of it. This article demonstrates the use of logical models to analyze data from different OSNs, based on a generic conceptual model that reflects a general definition of social networks. These examples aim to show the feasibility and advantages of using the generic model as a basis for specific OSN models, to support the analyses performed from the data extracted.